A novel full‐length two‐domain KIR2DL5A allele isolated in Zimbabwean samples: KIR2DL5A*0010104. (30th March 2020) - van Pul, Lisa; Majonga, Edith; Ferrand, Rashida; Rowland‐Jones, Sarah L.; Yindom, Louis‐Marie
Abstract : The novel allele KIR2DL5A*0010104 differs from that of KIR2DL5A*0010101 with eight single intronic nucleotide changes.